Alstonia angustiloba Progeny Trial to Support the Provision of Improved Seed (Uji Keturunan Pulai Darat (Alstonia angustiloba Miq.) untuk Mendukung Penyediaan Sumber Benih Unggul) - Mashudi, Mashudi; Adinugraha, Hamdan Adma (Balai Penelitian Kehutanan Manado, 2014)
The aim of this experiment was to identify of survival percentage, height plant and stem diameter of Alstonia angustiloba progeny trial at 2 year old to support the provision of improved seed. This experiment was arranged in randomized complete block design. The research used 2 factors, i.e. population sources (Carita-Banten, Pendopo-Muara Enim, Lubuk Linggau-Musi Rawas and Solok-West Sumatera) and parent trees (43 parent trees). In this experiment, parent trees factor was nested in the population sources. The result shodwed that survival percentage, height plant and stem diameter of Alstonia angustiloba progeny trial at 2 years old in Wonogiri were 82.07 %, 2.43 m and 2.85 cm, respectively.